An online image analysis tool for science education - Raeside, L.; Busschots, B.; Waddington, S.; Keating, J.G. (Computers and education, 2008)
This paper describes an online image analysis tool developed as part of an iterative, user-centered development of an online Virtual Learning Environment (VLE) called the Education through Virtual Experience (EVE) Portal. The VLE provides a Web portal through which schoolchildren and their teachers create scientific proposals, retrieve images and other resources, and produce collaborative scientific papers summarizing their learning experiences. The VLE underwent substantive formative testing involving over 200 schoolchildren producing over 50 collaboratively written research papers. Detailed analysis of these research papers identified some shortfalls toward the goal of producing authentic scientific engagement. The absence of data collection and data analysis within these research papers was disappointing despite having scheduled time for this activity and having several professional imaging tools available. The post-evaluation analyses have enabled the development team to identify specific design flaws in the previous VLE and have shaped the design of the new custom-built tool. The success of the tool will be born out through content analysis of future collaboratively written student papers.